2015
DOI: 10.1021/acs.energyfuels.5b00657
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Subfractions Responsible for Stabilizing Water-in-Crude Oil Emulsions. Part 2: Molecular Representations and Molecular Dynamics Simulations

Abstract: After successful isolation of the most interfacially active subfraction of asphaltenes (IAA) reported in part one of this series of publications, comprehensive chemical analyses including ES-MS, elemental analysis, FTIR and NMR were used to determine how the molecular fingerprint features of IAA are different from those of the remaining asphaltenes (RA).Compared with RA, the IAA molecules were shown to have higher molecular weight and higher contents of heteroatoms (e.g., three times higher oxygen content).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
147
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(167 citation statements)
references
References 50 publications
20
147
0
Order By: Relevance
“…86 The molecular weight distribution of IAA peaked within the range of 1,000-1,200 Da, while the average molecular weight of RA was centered at about 700-750 Da, which is in good agreement with recent asphaltene studies. 30 The elemental analysis showed similar carbon, hydrogen, nitrogen, and sulfur contents for two subfractions; however, the oxygen content of IAA (5.54 wt%) is three times higher than that of RA (1.68 wt%).…”
Section: Chemical Compositionssupporting
confidence: 90%
See 1 more Smart Citation
“…86 The molecular weight distribution of IAA peaked within the range of 1,000-1,200 Da, while the average molecular weight of RA was centered at about 700-750 Da, which is in good agreement with recent asphaltene studies. 30 The elemental analysis showed similar carbon, hydrogen, nitrogen, and sulfur contents for two subfractions; however, the oxygen content of IAA (5.54 wt%) is three times higher than that of RA (1.68 wt%).…”
Section: Chemical Compositionssupporting
confidence: 90%
“…It was reported that rather than whole asphaltenes, only a subfraction of asphaltenes is more likely the real contributor to the stabilization of W/O emulsions. 26,[80][81][82][83][84][85][86] The asphaltenes adsorbed onto clays have also been found to be different in composition from whole asphaltenes. 70,[75][76][77] Therefore, it is important to find ways to extract and study these particular species from asphaltenes, which are mainly responsible for the relevant issues of interest.…”
Section: Extended-sara (E-sara)mentioning
confidence: 99%
“…39 Several recent studies highlighted chemical and structural differences between asphaltenes that strongly adsorb at the oil-water and oil-solid interfaces and those remaining in the bulk oil. 40,41,42 An extended SARA analysis 33 where asphaltenes are fractionated and characterized according to their adsorption affinity confirmed differences between adsorbed asphaltenes and whole asphaltenes. In particular, asphaltenes strongly partitioned at the oil-water interface contain a particularly high oxygen content, which led to the increased presence of sulfoxide groups.…”
Section: Introductionmentioning
confidence: 86%
“…Only very recently have molecular dynamics simulations been applied to the study of asphaltenes at the oil/water interface. Mikami et al [124], Liu et al [125], as well as Yang et al [126] used atomistically-detailed simulations to study this system. In [124,125], the previously mentioned QMR-based model asphaltenes were employed, whereas in [126], two different model asphaltenes were proposed based on experimental measurements and used in simulations.…”
Section: Nanoscale: Validationmentioning
confidence: 99%
“…Mikami et al [124], Liu et al [125], as well as Yang et al [126] used atomistically-detailed simulations to study this system. In [124,125], the previously mentioned QMR-based model asphaltenes were employed, whereas in [126], two different model asphaltenes were proposed based on experimental measurements and used in simulations. These studies highlight the significant challenge encountered when using an atomistically-detailed approach: one is either confined to very few asphaltene molecules [126] or very short timescales [124,125] due to the high computational cost.…”
Section: Nanoscale: Validationmentioning
confidence: 99%